A comparative Study of the effect of Vitamin E and Zinc sulfate on Some Physiological and biochemical Parameters in the albino Rabbits males - orally vaccinated with Tramadol - Muneef Saab Ahmed Sachit Aljanabi (Tikrit Journal of Pure Science, 2023)
This research aims at investigating the therapeutic effect of Vitamin E and Zinc sulfate on some physiological and biochemical parameters in the albino rabbits males orally vaccinated with Tramadol (75 mg/kg). After being vaccinated, the rabbits were anesthetized and dissected to take autopsies from their livers and kidneys. Samples of blood were taken and serum was ready for the physiological and biochemical tests. The results how that Tramadol has obvious negative effects on the rabbits. That is, the concentrations of the protein for the total albumin have decreased (p≤ 0.01), whereas the concentrations of the Cryglobulinemia increased 9in the rabbits vaccinated with Tramadol)  compared with the control group. As for those vaccinated with only vitamin E and Zinc sulfate, the study shows that there is an increase in the protein concentration for the albumin, whereas Urea and Uric Acid in those vaccinated with Tramadol very high (p≤ 0.01), unlike those vaccinated with only vitamin E and Zinc sulfate in comparison with the controlling group. As for the liver enzymes (ALP, ALT, AST), their effectiveness has increased significantly  in the serum of those vaccinated with Tramado to those vaccinated with only vitamin E and Zinc sulfate. The lipid profile was negatively affected in the rabbits vaccinated with Tramadol, that is, it is increased significantly (p≤ 0.01), except the lipid proteins of high density (HDL-C) in comparison with the controlling group. It has been noticed that sex hormones in the serum of those vaccinated with Tramadol (p≤ 0.01), in comparison with the controlling group, unlike those vaccinated with only vitamin E and Zinc sulfate, that is, they increased significantly in the serum in comparison with the controlling group.